2009
DOI: 10.1111/j.1749-6632.2009.04981.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucocorticoids on Mood, Memory, and the Hippocampus

Abstract: Corticosteroids, such as prednisone and dexamethasone, are commonly prescribed medications that suppress the immune system and decrease inflammation. Common side effects of long-term treatment with corticosteroids include weight gain, osteoporosis, and diabetes mellitus. This paper reviews the literature on psychiatric and cognitive changes during corticosteroid therapy and potential treatment options. Hypomania and mania are the most common mood changes during acute corticosteroid therapy, although depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(138 citation statements)
references
References 105 publications
7
122
0
9
Order By: Relevance
“…In our study, 16 % of the patients were treated with glucocorticosteroids, which are known to have implications for mood system ( 40 ). Indeed, in this study, the use of steroids was found to be associated with a signifi cantly increased risk of developing anxiety disorders.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 62%
“…In our study, 16 % of the patients were treated with glucocorticosteroids, which are known to have implications for mood system ( 40 ). Indeed, in this study, the use of steroids was found to be associated with a signifi cantly increased risk of developing anxiety disorders.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 62%
“…Following successful treatment of hypercortisolism, signs and symptoms improve substantially. However, prolonged, excessive exposure to glucocorticoids may have long-lasting adverse effects on behavioral and cognitive functions, due to functional and structural alterations in specific brain target areas (1)(2)(3)(4). Furthermore, these patients do not completely return to their premorbid level of functioning, and quality of life (QoL) is persistently impaired despite long-term cure of CS (5).…”
Section: Introductionmentioning
confidence: 99%
“…[104] The severity of memory impairment is correlated to dose and duration of use. [105] Primary prevention strategies might include the implementation of hippocampal-sparing whole brain radiation therapy, prophylactic use of the N-methyl-Daspartate receptor modulator memantine, or blocking the RAAS cascade. Assessment and treatment of depression is an important strategy, including appropriate pharmaceutical or psychological treatments.…”
Section: Quality Of Life and Neurocognitionmentioning
confidence: 99%